CMOS Compatible Growth of High Quality Ge, SiGe and SiGeSn for Photonic Device Applications. (8th September 2015) - Alher, Murtadha A.; Mosleh, Aboozar; Cousar, Larry; Dou, Wei; Grant, Perry; Ghetmiri, Seyed Amir; Al-Kabi, Sattar; Du, Wei; Benamara, Mourad; Li, Baohua; Mortazavi, Mansour; Yu, Shui-Qing; et al.
Abstract : Germanium films were deposited on silicon substrate by an ultra-high vacuum chemical vapor deposition system using GeH4 as Ge precursor and different carrier gases (Ar, N2 and H2 ). Silicon-germanium and SiGeSn films were deposited using optimized growth conditions of Ge growth. Silane and SnD4 were used as precursors for Si and Sn, respectively. A complete study of SiGe growth at chamber pressure from 0.1 to 1.0 torr and at temperatures from 350-450ºC for different SiH4 flow rate is performed. Silicon incorporation in Ge films varied from 1% to 17%. Tin incorporation of 2% was observed in the films with 17% Si incorporation. Investigation of film quality has been done using etch pit measurement, scanning electron microscopy and transmission electron microscopy. Threading dislocation density for Ge, SiGe and SiGeSn films were 1.7×10 7 cm -2, 2.3 ×10 7 cm -2 and 4.0 ×10 7 cm -2, respectively.